Students’ reflections on integrating theory and practice in translation: A qualitative study of an academic–practitioner collaborative course - Kristanto, TMA; Sudirman, Anselmus (English Language Teaching Educational Journal, 2025)
This research examines students' reflections on the integration of theoretical knowledge and practical application within a translation curriculum that combines academic instruction with sessions led by industry practitioners. Sixteen students in their fifth semester from the English Education Department of Universitas Sarjanawiyata Tamansiswa participated in this investigation, having engaged in both theoretical lectures and practical workshops as components of the Principles in Translating and Interpreting course. Data were obtained through reflective journals and semi-structured interviews, subsequently undergoing thematic analysis. The results indicate that academic sessions provided crucial theoretical foundations, whereas practitioner-led activities facilitated students in applying, testing, and attaining a deeper comprehension of these theories within authentic translation environments. Systematic reflection enabled students to identify challenges, develop effective translation strategies, and enhance their confidence and professional mindset. Many participants reported shifting from seeing themselves solely as students to perceiving themselves as emerging professionals. Supported by recent research highlighting reflective practice as a catalyst for developing professional competence and learner autonomy, these findings underscore the value of designing translation curricula that integrate theory, real-world practice, and structured reflection. The study further suggests that such integration can strengthen students’ readiness for the demands of professional translation work and guide curriculum developers in creating more practice-oriented, reflective learning environments.